Understanding journalism : a guide to issues - Wilson, John, 1936 August 3- (Routledge, 1996)
Never has the media been so critically regarded as at the present time. Documenting many areas of debate and dispute between journalists, the media, public organizations and politicians, the author identifies why conflicts will continue. Covering topics from government bias to censorship, official secrets to freedom of information and animal rights to obscenity, this highly informative work is a valuable guide to all those involved in journalism and the media.